The Legacy of H.M. Rasyid Bancin: Modernizing Islamic Education in Indonesia - Bako, Abdul Aziz Azhar; Arsyad, Junaidi; Hanum, Azizah (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the relevance of H. Rasyid Bansin’s contributions to Islamic education and their significance for contemporary educational practices. Employing a qualitative approach with a character-study-oriented design, this research collected data through face-to-face interactions and field engagements at the research site. The methodology followed established steps in figure study research to ensure systematic analysis. The findings highlight the enduring relevance of H. Rasyid Bansin’s contributions, particularly through his establishment of modern Islamic boarding schools, integration of foreign language instruction (Arabic and English), promotion of science and technology, founding of formal schools (MTs and MA levels), and cultivation of resilient, socially conscious students. Unlike prior studies that focus solely on the role of historical figures in Islamic education, this research specifically analyzes the relevance of contributions, offering a fresh perspective on how past innovations can inform modern pedagogical practices. The study provides actionable insights for contemporary Islamic educational institutions, suggesting ways to adapt H. Rasyid Bansin’s strategies such as multilingual curricula and holistic student development to current needs. This research enriches the theoretical discourse on Islamic education by bridging historical and modern perspectives. It also serves as a foundation for future studies on the intersection of tradition and innovation in religious education.